2008
DOI: 10.1007/s00125-008-1067-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cardiorespiratory fitness, low physical activity and an urban environment are independently associated with increased cardiovascular risk in children

Abstract: Aims/hypothesis To assist in the development of preventive strategies, we studied whether the neighbourhood environment or modifiable behavioural parameters, including cardiorespiratory fitness (CRF) and physical activity (PA), are independently associated with obesity and metabolic risk markers in children. Methods We carried out a cross-sectional analysis of 502 randomly selected first and fifth grade urban and rural Swiss schoolchildren with regard to CRF, PA and the neighbourhood (rural vs urban) environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
46
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 35 publications
(72 reference statements)
11
46
0
6
Order By: Relevance
“…These results are similar to several other studies in the pediatric population 1011 , 23 , 24 Kriemler et al 9 found an inverse association between aerobic fitness and the sum of four skinfolds, insulin resistance, and metabolic risk; furthermore, they observed a 6% reduction in insulin resistance for each increase of one stage in an aerobic fitness test.…”
Section: Discussionsupporting
confidence: 91%
“…These results are similar to several other studies in the pediatric population 1011 , 23 , 24 Kriemler et al 9 found an inverse association between aerobic fitness and the sum of four skinfolds, insulin resistance, and metabolic risk; furthermore, they observed a 6% reduction in insulin resistance for each increase of one stage in an aerobic fitness test.…”
Section: Discussionsupporting
confidence: 91%
“…Ekelund et al 22 showed an inverse correlation (partial r=–0.11) in 1709 European children and adolescents aged 9 and 15 years old from the European Youth Heart Study. In a Swiss sample, accelerometer-measured sedentary activity was not related to CRF 23. It must be noted that the main purposes of these two studies were not to examine the associations between sedentary time and CRF and, in addition, associations were not controlled for body fat and physical activity measures.…”
Section: Discussionmentioning
confidence: 92%
“…Minimising the decline in CRF during adolescence may have a positive impact on adulthood health 9. It is not known if engagement in physical activity counteracts the effect of sedentary time on CRF during adolescence 22 23…”
Section: Introductionmentioning
confidence: 99%
“…Among the detrimental consequences of childhood overweight on current and future health, children and adolescents with overweight are less fit than their leaner peers 13. Also, overweight may lead to inactivity and not be the result of it 4.…”
Section: Introductionmentioning
confidence: 99%